Sequence Variations of the Latent Membrane Protein 1 of Epstein-Barr Virus Isolates from Cases of Malaysian Nasopharyngeal Carcinoma: A Preliminary Study - Eng-Lai, Tan; C.S, Chang; G.G, Krishnan; C.K, Sam (Malaysian Journal of Science, 2007)
The nucleotide sequences of the Epstein-Barr virus (EBY) latent membrane protein 1 (LMP1) genes from throat washing samples of six Malaysian nasopharyngeal carcinoma (NPC) patients were determined. The full-length LMPI gene was amplified by PCR in two segments; exon A to exon B (exons AB) and exon C, and cloned into pcDNA3.1/V5-HisÂ©TOPOÂ®TA plasmid for DNA sequencing. Full length LMP1 DNA sequences were obtained from three throat wash samples while in the remaining three samples, only the exons AB was successfully sequenced. DNA sequence alignment showed that the three completely sequenced LMP1 genes analyzed had, on average, 96% homology with the LMP1 sequence of the EBV B95.8 wild-type strain. The majority of the point mutations identified were common to those reported for the EBV isolates from China and Taiwan. These mutations were mainly clustered at the transmembrane region. However, there were a few base substitutions, which were unique to individual samples. All six samples displayed a loss of Xho1 restriction site at the amino terminal of the LMP1 gene. In three of the six samples (P8, P17 and P58), the 15 bp and 30 bp deletions at the carboxyl terminal were detected. As a result of the 15 bp deletion, the LMP1 genes from two of the three samples (P17 and P58) displayed four perfect repeats while in the remaining sample (P8), five perfect repeats were detected. Overall, of the amino acid sequences of the six LMP1 genes analyzed showed the highest homology to the LMP1 gene derived from the China 1 EBV strain.